2016
DOI: 10.1007/s11481-016-9690-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell Mediated Photothermal Therapy of Brain Tumors

Abstract: Gold based nanoparticles with strong near infra-red (NIR) absorption are ideally suited for photothermal therapy (PTT) of brain tumors. The goal of PTT is to induce rapid heating in tumor tissues while minimizing thermal diffusion to normal brain. PTT efficacy is sensitively dependent on both nanoparticle concentration and distribution in tumor tissues. Nanoparticle delivery via passive approaches such as the enhanced permeability and retention (EPR) effect is unlikely to achieve sufficient nanoparticle concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The use of laser wavelength in the ‘tissue optical window’ (700–1000 nm) minimizes tissue heating, while Au NPs have strong and tunable absorption in the NIR region. Therefore, Au NPs and NIR can be used to facilitate selective heating of tumours with NPs [ 127 ]. Gold nanoparticles with thiol and amine groups can be functionalized with targeted antibodies or drug products.…”
Section: Cancer Therapymentioning
confidence: 99%
“…The use of laser wavelength in the ‘tissue optical window’ (700–1000 nm) minimizes tissue heating, while Au NPs have strong and tunable absorption in the NIR region. Therefore, Au NPs and NIR can be used to facilitate selective heating of tumours with NPs [ 127 ]. Gold nanoparticles with thiol and amine groups can be functionalized with targeted antibodies or drug products.…”
Section: Cancer Therapymentioning
confidence: 99%
“…For instance, Eldridge et al have demonstrated the sound efficacy of PTT against GBM by near-infrared (NIR) irradiation of multiwalled carbon nanotubes in an in vitro tumor spheroid model 23 . Due to their innate tumor-tropic migration behavior, macrophages loaded with Au nanoshells have also been adopted for NIR-induced thermal ablation of GBM 24 . A delayed growth of GBM in rats receiving the cell-based photothermal therapy was observed compared to the untreated group.…”
Section: Introductionmentioning
confidence: 99%
“…At a wavelength of 0.6 -1.4 µm and over, the skin, muscles and bones, parenchymal organs and highly vascularized tissue absorb 25-40%, 30-80%, and up to 100% of radiation, respectively [19]. IR laser radiation at the doses of 5 -40 J/cm 2 are often used for local laser hyperthermia of neoplasms inducing coagulative necrosis of the tumor with minimal damage to surrounding healthy tissues [20].…”
Section: Introductionmentioning
confidence: 99%